Processing of Complement Coercion With Aspectual Verbs in Mandarin Chinese: Evidence From a Self-Paced Reading Study - Xue, Wenting; Liu, Meichun; Politzer-Ahles, Stephen (Frontiers in Psychology, 2021)
This study examines whether Mandarin complement coercion sentences with aspectual verbs will elicit processing difficulty during real-time comprehension. Complement coercion is a linguistic phenomenon in which certain verbs (e.g., start, enjoy), requiring an event-denoting complement, are combined with an entity-denoting complement (e.g., book), as in The author started a book. Previous studies have reported that the entity-denoting complement elicited processing difficulty following verbs that require event argument compared with verbs that do not (e.g., The author wrote a book). While the processing of complement coercion has been extensively studied in Indo-European languages such as English and German, it is relatively under-researched in Sino-Tibetan languages such as Mandarin Chinese. Given the fact that there are many linguistic elements behaving distinctly in the different language families, for instance, verbs with respect to their semantic properties and syntactic representations of the complement, it is meaningful to investigate whether or not the existing linguistic differences have any effect on the processing of complement coercion in Mandarin. With this research goal, we recorded self-paced reading time of 61 native Mandarin speakers to investigate the processing of the entity-denoting complement in sentences with three different verb types (aspectual verbs which require an event-denoting complement, preferred verbs which denote a preferred interpretation of the aspectual expressions, and non-preferred verbs which denote a non-preferred but plausible interpretation of the aspectual expressions), as exemplified in 顾客开始/填写/查看这份问卷gù-kè kāi-shǐ/tián-xiě/chá-kàn zhè-fèn wèn-juàn ‘The customer started/filled in/checked the questionnaire’. It was found that the entity noun complement (e.g., 这份问卷 zhè-fèn wèn-juàn ‘the questionnaire’) elicited significantly longer reading times in coercion sentences than non-coercion counterparts. The results are compatible with the previous findings in English that complement coercion sentences impose processing cost during real-time comprehension. The study contributes empirical evidence to coercion studies cross-linguistically.